2016
DOI: 10.5664/jcsm.6126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP Therapy on Symptoms of Nocturnal Gastroesophageal Reflux among Patients with Obstructive Sleep Apnea

Abstract: Study Objectives: Nocturnal gastroesophageal reflux (nGER) is common among patients with obstructive sleep apnea (OSA). Previous studies demonstrated that continuous positive airway pressure (CPAP) reduces symptoms of nGER. However, improvement in nGER symptoms based on objective CPAP compliance has not been documented. We have examined the polysomnographic characteristics of patients with nGER and OSA and looked for association of OSA severity and CPAP compliance with improvement in nGER symptoms. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…(2) AHI and weak acid re ux were both signi cantly correlated with chronic cough, AHI was also correlated with weak acid re ux. This ndings are consistent with other studies that CPAP treatment can improve GER [10,18] and daytime sleepiness [10] . Previous studies investigated the effect of CPAP on GER and OSA, but there had been no analysis focus on the effect of CPAP on chronic cough in OSA concomitant GER patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(2) AHI and weak acid re ux were both signi cantly correlated with chronic cough, AHI was also correlated with weak acid re ux. This ndings are consistent with other studies that CPAP treatment can improve GER [10,18] and daytime sleepiness [10] . Previous studies investigated the effect of CPAP on GER and OSA, but there had been no analysis focus on the effect of CPAP on chronic cough in OSA concomitant GER patients.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study have concluded that proton pump inhibitor (PPI) therapy for GER can not improve cough in GER patients [9] . Continuous positive airway pressure (CPAP) has been shown to improve GER events in OSA patients [10] . Unfortunately, as far as OSA and GER-related cough is concerned, the therapeutic management remains largely empirical.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies [ 50 52 ] have shown an improvement in snoring, gastro-esophageal reflux and oxygen saturation with CPAP treatment. In our case, they were found among the characteristics with the highest stability scores for the best pipelines of month-0 and month-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, in nonpregnant patients, adherence to CPAP therapy may actually decrease GERD symptoms. 107 Some patients on CPAP therapy do experience aerophagia, introduction of air into the esophagus, which results in gastrointestinal discomfort and belching. Aerophagia may be related to decreased lower esophageal sphincter tone, which could be of concern in pregnant patients on CPAP.…”
Section: Peripartum Management Of Osamentioning
confidence: 99%